Inhibition of hemagglutinin-glycan interaction by complexes of oligoribonucleotides with D-mannitol - Melnichuk, N.S.; Tkachuk, Z.Yu. (Reports of the National Academy of Sciences of Ukraine, 2018)
By the results of the indirect determination of the amount of influenza virus titer by the hemagglutination assay, it is found that oligoribonucleotides-D-mannitol (ORNs-D-M) complexes interfere with HA–glycan interactions. The infectivity of influenza virus H1N1 (A/FM/1/47) decreases after the incubation with ORNs-D-M. It is shown that ORNs-D-M possess a direct virucidal action.